SOSIALISASI GREEN PACKAGING DI DESA DARMAWANGI KECAMATAN TOMO KABUPATEN SUMEDANG - Yosini Dekiana; Sri Fatimah; Lucyana Trimo; Mohamad Djali; Endah Wulandari (Universitas Galuh Ciamis, 2021)
To overcome plastic waste, the Government of Indonesia has issued Presidential Regulation No. 83 of 2018. Also Bandung Regional Regulation No. 17 of 2018 on reducing the use of plastic bags. A number of strategies have been carried out but until now the implementation has not run optimally. Partners are empowered with training on the importance of green packaging to reduce plastic waste. It is hoped that if the partner has a cohesiveness in managing his business, a strong motivation in entrepreneurship, has a potential product to be marketed, know the green packaging and know the tarket of the green consumer consumer market, then improved the product to green products. Handling the environmental issues of the paper industry through the use of non-wood paper base material becomes an interesting thing by utilizing annual crops or agricultural plant residues to be used as the basic material of paper and pulp. Community service in Darmawangi village, Tomo District, Sumedang regency about green packaging began by giving the material